Current status on clinical applications of magnesium-based orthopaedic implants: A review from clinical translational perspective. (January 2017) - Zhao, Dewei; Witte, Frank; Lu, Faqiang; Wang, Jiali; Li, Junlei; Qin, Ling
Abstract: As a new generation of medical metallic material, magnesium (Mg) and its alloys with or without surface coating have attracted a great deal of attention due to its biodegradability and potential for avoiding a removal operation after the implant has fulfilled its function for surgical fixation of injured musculoskeletal tissues. Although a few clinical cases on Mg-based orthopaedic implants were reported more than a century ago, it was not until recently that clinical trials using these implants with improved physicochemical properties were carried out in Germany, China and Korea for bone fracture fixation. The promising results so far suggest a bright future for biodegradable Mg-based orthopaedic implants and would warrant large scale phase II/III studies. Given the increasing interest on this emerging biomaterials and intense effort to improve its properties for various clinical applications, this review covers the evolution, current strategies, and future perspectives in the development of Mg-based orthopaedic implants. We also highlight a few clinical cases performed in China that may be unfamiliar to the general orthopaedic community.